A Woman’s Expression for Freedom in Sabrina Carpenter’s “Feather”: A Radical Feminist Reading - Pebrawaninggil, Ganeshiwi Intan; Nurhayati, Sulasih (Universitas Pahlawan Tuanku Tambusai, 2025)
The depiction of female liberation in mainstream media has emerged as a critical focus within feminist discourse. This article examines how Sabrina Carpenter's music video